The reaction against fourth feminist way. The (re)legitimation of sexual violence in post ‹‹Me too››. Philosophical keys to understanding the incomprehensible - Miguel Álvarez, Ana de (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
One of the features of the fourth feminist wave has been the identification, critique and delegitimization of sexual violence. From a philosophical perspective, a relevant question is how this violence, as archaic as it is represented with airs of transgression and modernity, has been and continues to be possible. This article tries to analyze and understand the following: 1) the belief system that eroticizes, aestheticizes and legitimizes sexual desire associated with violence, and 2) the consequences of learning sexual violence as a factor that reproduces inequality between women and men. The article has the final purpose of leaving an open question for discussion. If the construction of the theoretical framework «gender violence» implied the radical separation of love and violence, would it be possible and desirable to elaborate a theoretical framework that radically separates sexuality and violence?
Keywords: gender violence; sexual violence; rape culture; pornography; feminist theory